Metabolic Reprogramming of Cancer by Chemicals that Target Glutaminase Isoenzymes. - Mates-Sánchez, José Manuel; Campos-Sandoval, José Ángel; De los Santos-Jiménez, Juan; Segura-Checa, Juan Antonio; Alonso-Carrión, Francisco José; Márquez-Gómez, Javier (BenthamScience, 2020)
Background: Metabolic reprogramming of tumours is a hallmark of cancer. Among the changes in the metabolic network of cancer cells, glutaminolysis is a key reaction altered in neoplasms. Glutaminase proteins control the first step in glutamine metabolism and their expression correlates with malignancy and growth rate of a great variety of cancers. The two types of glutaminase isoenzymes, GLS and GLS2, differ in their expression patterns and functional roles: GLS has oncogenic properties and GLS2 has been described as a tumour suppressor factor. Results: We have focused on glutaminase connections with key oncogenes and tumour suppressor genes. Targeting glutaminase isoenzymes includes different strategies aimed at deactivating the rewiring of cancer metabolism. In addition, we found a long list of metabolic enzymes, transcription factors and signalling pathways dealing with glutaminase. On the other hand, a number of chemicals have been described as isoenzyme-specific inhibitors of GLS and/or GLS2 isoforms. These molecules are being characterized as synergic and therapeutic agents in many types of tumours. Conclusion: This review states the metabolic pathways that are rewired in cancer, the roles of glutaminase isoforms in cancer, as well as the metabolic circuits regulated by glutaminases. We also show the plethora of anticancer drugs that specifically inhibit glutaminase isoenzymes for treating several sets of cancer.
Keywords: Cáncer - Aspectos moleculares; Antiangiogénicos; Cancer metabolism; Combinatory therapy; Glutaminase inhibitors; Glutaminase isoenzymes; Glutamine; Metabolic reprogramming